The confidence and knowledge of health practitioners when interacting with people with aphasia in a hospital setting. Issue 11 (22nd May 2018) - Cameron, Ashley; McPhail, Steven; Hudson, Kyla; Fleming, Jennifer; Lethlean, Jennifer; Tan, Ngang Ju; Finch, Emma
Abstract: Purpose: The aim of the study was to describe and compare the confidence and knowledge of health professionals (HPs) with and without specialized speech-language training for communicating with people with aphasia (PWA) in a metropolitan hospital setting. Methods: Ninety HPs from multidisciplinary teams completed a customized survey to identify their demographic information, knowledge of aphasia, current use of supported conversation strategies and overall communication confidence when interacting with PWA using a 100 mm visual analogue scale (VAS) to rate open-ended questions. Conventional descriptive statistics were used to examine the demographic information. Descriptive statistics and the Mann–Whitney U test were used to analyse VAS confidence rating data. The responses to the open-ended survey questions were grouped into four previously identified key categories. Results: The HPs consisted of 22 (24.4%) participants who were speech-language pathologists and 68 (75.6%) participants from other disciplines (non-speech-language pathology HPs, non-SLP HPs). The non-SLP HPs reported significantly lower confidence levels ( U = 159.0, p < 0.001, two-tailed) and identified fewer strategies for communicating effectively with PWA than the trained speech-language pathologists. The non-SLP HPs identified a median of two strategies identified [interquartile range (IQR) 1–3] in contrast to the speech-language pathologists who identified a median of eight strategies (IQR 7–12). Conclusion: These findings suggest that HPs, particularly those without specialized communication education, are likely to benefit from formal training to enhance their confidence, skills and ability to successfully communicate with PWA in their work environment. This may in turn increase the involvement of PWA in their health care decisions. Implications for Rehabilitation: Interventions to remediate health professional's (particularly non-speech-language pathology health professionals) lower levels of confidence and ability to communicate with PWA may ultimately help ensure equal access for PWA. Promote informed collaborative decision-making, and foster patient-centred care within the health care setting.